2022
DOI: 10.3389/fneur.2021.734251
|View full text |Cite
|
Sign up to set email alerts
|

Apathy, Executive Function, and Emotion Recognition Are the Main Drivers of Functional Impairment in Behavioral Variant of Frontotemporal Dementia

Abstract: Background: The cognitive and neuropsychiatric deficits present in patients with behavioral variant frontotemporal dementia (bvFTD) are associated with loss of functionality in the activities of daily living (ADLs). The main purpose of this study was to examine and explore the association between the cognitive and neuropsychiatric features that might prompt functional impairment of basic, instrumental, and advanced ADL domains in patients with bvFTD.Methods: A retrospective cross-sectional study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 68 publications
0
29
0
Order By: Relevance
“…More specifically, apathy was found to be the most robust behavioral correlate of functional impairment in both bvFTD and SemD (Kipps et al, 2009;O'Connor et al, 2016a;Musa Salech et al, 2022). Stereotypical behavior and disinhibition has also been associated with poor functional outcomes, but only in bvFTD (O'Connor et al, 2016b;Musa Salech et al, 2022). With respect to other behavioral symptoms that correlate with the functional status in FTD, literature suggests that hallucinations and anxiety are associated with decreased functional capacity in bvFTD, whereas delusions and eating disorders seem to contribute to functional decline in nfvPPA (Moheb et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…More specifically, apathy was found to be the most robust behavioral correlate of functional impairment in both bvFTD and SemD (Kipps et al, 2009;O'Connor et al, 2016a;Musa Salech et al, 2022). Stereotypical behavior and disinhibition has also been associated with poor functional outcomes, but only in bvFTD (O'Connor et al, 2016b;Musa Salech et al, 2022). With respect to other behavioral symptoms that correlate with the functional status in FTD, literature suggests that hallucinations and anxiety are associated with decreased functional capacity in bvFTD, whereas delusions and eating disorders seem to contribute to functional decline in nfvPPA (Moheb et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 5 years after symptom onset, the vast majority of bvFTD patients tend to develop severe functional impairment (Mioshi et al, 2007). However, information on the functional status of patients with FTD is relatively sparse and focuses mainly on the behavioral-variant of FTD (Josephs et al, 2011;Lima-Silva et al, 2013, 2015aMusa Salech et al, 2022). Research has shown that, as happens in AD, FTD initially affects instrumental activities of daily living (IADLs), while decline in basic activities of daily living (BADLs) develops later in the course of the disease (Mioshi et al, 2010;Musa Salech et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations